Effect of truncal vagotomy and/or pyloroplasty on gallbladder amptying and plasma CCK in humans - Mahir ÖZMEN; Mükerrem ÇETE; RS PATANKAR; A. SANDERSON; CD JOHNSON (Turkish Journal of Gastroenterology, 2019)
-